Les sources nativement numériques: Enjeux de documentation et de redocumentarisation. - Schafer, Valérie; Clavert, Frédéric; Muller, Caroline (Annales: Histoire, Sciences Sociales, 2025)
The creation, preservation, and exploitation of born-digital sources involve processes not only of documentation but also of "redocumentation"—for instance, producing additional metadata that determines their archiving and accessibility, or keeping track of the operations required to reconstruct documents in different forms, sometimes at the cost of a degree of transformation. Managing this "reborn" heritage requires a wide range of technical operations, conducted by numerous institutions and actors (libraries and archives, activist and participatory initiatives, private and international stakeholders) and raises issues of accessibility, sharing, contextualization, and openness that influence the scholarly use of born-digital archives. Drawing primarily on the archiving of the web and social media, but also on that of source code, CD-ROMs, and emails, this article explores the logics of documentation and redocumentation, as well as the practices and tensions at work. An awareness of these logics can prove decisive for research in history and, more broadly, in the humanities and social sciences, since they not only support such research but also allow for greater contextualization.